2020
DOI: 10.24275/rmiq/bio1022
|View full text |Cite
|
Sign up to set email alerts
|

Termiticidal activity of mycosynthesized silver nanoparticles from Aspergillus fumigatus BTCB15

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In recent years, the biosynthesis of AgNPs by microorganisms, plants, and their extracts have attracted considerable attention. At present, it has been found that a variety of microorganisms, including bacteria, [3,4] yeast, [5] and fungi, [6,7] have the ability to synthesize nanoparticles. Microbial system-mediated (bacterial and fungal) synthesis of nanoparticles has some advantages over other methods because they are easy to control during the synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the biosynthesis of AgNPs by microorganisms, plants, and their extracts have attracted considerable attention. At present, it has been found that a variety of microorganisms, including bacteria, [3,4] yeast, [5] and fungi, [6,7] have the ability to synthesize nanoparticles. Microbial system-mediated (bacterial and fungal) synthesis of nanoparticles has some advantages over other methods because they are easy to control during the synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…The application of silver nanoparticles (AgNPs) has become increasingly popular for enhancing diverse wood properties, including resistance to biological degradation, water absorption capacity, and dimensional stability. These improvements are achieved through both depth and surface treatments, spanning various concentrations of AgNPs [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%